2005
DOI: 10.2337/diabetes.54.4.1056
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of Glucose-Dependent Insulinotropic Polypeptide and Glucagon-Like Peptide-1 on Insulin Secretion and Gut Motility

Abstract: ؊/؊ mice), we found that pretreatment with GIP in vivo failed to blunt the rise in blood glucose levels after oral glucose load. In Kir6.2 ؊/؊ mice, potentiation of insulin secretion by GIP in vivo was markedly attenuated, indicating that K ATP channels are essential in the insulinotropic effect of GIP. In contrast, pretreatment with glucagon-like peptide-1 (GLP-1) in Kir6.2 ؊/؊ mice potentiated insulin secretion and blunted the rise in blood glucose levels. We also found that GLP-1 inhibited gut motility wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 47 publications
6
97
2
1
Order By: Relevance
“…mice at 15 min after glucose loading were significantly higher than those in Kir6.2 C/C mice (PZ0.021) (Fig. 3a), and are consistent with results described in a previous report (Miki et al 2005). Plasma GIP levels at 15 min with voluntary feeding on dextrin were higher than those with voluntary feeding on standard chow in both Kir6.2 C/C mice and Kir6.2 K/K mice, indicating that carbohydrate is a powerful GIP secretagogue.…”
Section: Metabolism Of Glucose In K-cells Is Not Essential For Gip Sesupporting
confidence: 82%
See 1 more Smart Citation
“…mice at 15 min after glucose loading were significantly higher than those in Kir6.2 C/C mice (PZ0.021) (Fig. 3a), and are consistent with results described in a previous report (Miki et al 2005). Plasma GIP levels at 15 min with voluntary feeding on dextrin were higher than those with voluntary feeding on standard chow in both Kir6.2 C/C mice and Kir6.2 K/K mice, indicating that carbohydrate is a powerful GIP secretagogue.…”
Section: Metabolism Of Glucose In K-cells Is Not Essential For Gip Sesupporting
confidence: 82%
“…In contrast to GIIS, GIP secretion in response to oral glucose loading in Kir6.2 K/K mice is somewhat enhanced, compared with that in Kir6.2 C/C mice (Miki et al 2005). This indicates that the K ATP channels in K-cells are activated and involved in the suppression of glucose-induced GIP secretion in the physiological state.…”
Section: Introductionmentioning
confidence: 57%
“…ATP binds to the cytoplasmic side of K ir6.2 subunit in an Mg 2+ -dependent manner initiating a conformational change that results in closure of the channel (Gribble et al, 1998). Depolarization and deactivation of the K ATP channels are entirely responsible for the first phase of insulin secretion as illustrated by the K ATP knockout mice (Miki et al, 2005) and separately by the SUR1 knockout mice (Miki et al, 2005;Shiota et al, 2002). In humans, mutations in either K ir6.2 or K ATP result in a severe form of persistent hyperinsulinemic hypoglycemia of infancy (PHHI; Glaser et al, 1994).…”
Section: Potassium Channelsmentioning
confidence: 99%
“…In humans, mutations in either K ir6.2 or K ATP result in a severe form of persistent hyperinsulinemic hypoglycemia of infancy (PHHI; Glaser et al, 1994). By contrast, absence of K ATP channels in mice results in less severe symptoms where the mice are normoglycemic, displaying glucose intolerance only upon feeding or glucose challenge (Miki et al, 2005;Shiota et al, 2002).…”
Section: Potassium Channelsmentioning
confidence: 99%
“…We previously generated mice lacking Kir6.2, the pore subunit of the b-cell K ATP channel (Kir6.2 K/K ) (Miki et al 1998), and found that Kir6.2 K/K mice elicit no significant increase in insulin secretion in response to glucose using perifusion of isolated pancreatic islets (Miki et al 1998) and perfusion of pancreas (Miki et al 2005), both of which were performed under denervated, in vitro condition. In Sur1 K/K mice, which lack the regulatory subunit of the channel, only a very small amount of insulin in response to glucose is triggered, as assessed by perfusion of pancreas (Shiota et al 2002) and batch incubation of isolated pancreatic islets (Doliba et al 2004).…”
Section: Introductionmentioning
confidence: 99%